INDUCED PLURIPOTENT STEM CELLS: WHERE WE ARE CURRENTLY? - Rančić, Nemanja; Raščanin, Sanja; Miljković, Milijana; Jovanović, Mirjana (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Induced Pluripotent Stem Cells (iPSCs) are type of pluripotent stem cells generated by reprogramming an adult somatic cell genome to the stage of pluripotent stem cell in vitro by inducing a forced expression of specific transcription factors that are important for the maintenance of pluripotency such as Sox2, Oct3/4, c- Myc, KLF4; or using the similar set of four transcription factors Oct4, Sox2, Lin28 and Nanog. iPSCs seem to be very similar to Embryonic Stem Cells (ESCs) in terms of morphology, cell surface markers and gene expression levels, but recent studies have demonstrated some differences between the two cell types. However, iPSCs might have potential application in regenerative medicine, transplantation, drug testing, disease modeling, and avoidance of tissue rejection and with less ethical concern than ESCs. The aim of this paper is presenting the most important characteristics of the iPSCs which have therapeutic significance.